2016
DOI: 10.1063/1.4942032
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of the spatial distribution of laser-accelerated proton beams by varying the laser intensity distribution

Abstract: We report on a study of the spatial profile of proton beams produced through target normal sheath acceleration (TNSA) using at target foils and changing the laser intensity distribution on the target front surface. This is done by either defocusing a single laser pulse or by using a split-pulse setup and irradiating the target with two identical laser pulses with variable spatial separation. The resulting proton beam profile as well as the energy spectrum are recorded as functions of the focal spot size of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…No attempt was made to measure or mitigate spatio-temporal coupling effects 41 which, if present, would equally affect all shots. Similarly, non-uniformities in the defocused laser spot, which are known to manifest in the proton beam 42 , are presumed to affect the proton source equally for all shots. The 10 μm Au hemi was chosen as the proton source target because experience has shown it to be reliable and relatively free from instability-induced structures in the proton beam profile.…”
Section: Methodsmentioning
confidence: 99%
“…No attempt was made to measure or mitigate spatio-temporal coupling effects 41 which, if present, would equally affect all shots. Similarly, non-uniformities in the defocused laser spot, which are known to manifest in the proton beam 42 , are presumed to affect the proton source equally for all shots. The 10 μm Au hemi was chosen as the proton source target because experience has shown it to be reliable and relatively free from instability-induced structures in the proton beam profile.…”
Section: Methodsmentioning
confidence: 99%
“…This mechanism, known as target normal sheath acceleration (TNSA) 20,21 , being the most robust scheme for laser-proton acceleration and studied most widely for a variety of laser and target parameters 1,2123 , allows for direct manipulation of collective beam parameters like pointing and divergence. Influencing the symmetry of the accelerating electron sheath has been demonstrated by shaping of the focal spot 24,25 , by introducing a laser pulse front tilt 26 , or by micro-engineering of the target surface 4,2729 . The limitation of the lateral target size (so-called mass-limited targets with few 10 μm in diameter) has been pursued as a complementary approach confining the electron sheath.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the transverse spatial profile of the sheath field on the target-rear surface has a profound influence on the angular divergence of the accelerated proton beam. Using numerical simulations it has been shown that the diameter of the resultant proton beam at the detector can be reduced, if the transverse circular area of the sheath field on the rear side of the target is increased [26]. With micromachined targets, the laser interaction not only increases α eh , but also decreases l rem as the depth of the pit increases.…”
Section: Structures On 125 μM Thick Foilsmentioning
confidence: 99%
“…Focussing of the full proton beam down to a small spot has been demonstrated in the past using curved targets [24,25]. Recently, Aurand et al have demonstrated that the spatial distribution of the hot electrons on the rear side of the target and the transverse expansion of the electric sheath field has a profound effect on the angular divergence of the accelerated protons; the proton beam divergence can be reduced if the transverse spatial distribution of the electron sheath on the rear surface of the target is increased [26]. One way to reduce it is to defocus the laser on the target [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation